Qualitative reasoning about physical systems - Bobrow, Daniel G. (Daniel Gureasko), 1935- (North-Holland ; Sole distributors for the U.S.A. and Canada, MIT Press, 1984)
This volume brings together current work on qualitative reasoning. Its publication reflects the maturity of qualitative reasoning as a research area and the growing interest in problems of reasoning about physical systems. The papers present knowledge bases for a number of very different domains, including heat flow, transistors, and digital computation. A common theme of all these papers is explaining how physical systems work. An important shared criterion is that the behavioral description must be compositional, that is the description of a system's behavior must be derivable from the structure of the system. This material should be of interest to anyone concerned with automated reasoning about the real (physical) world.